A new fossil Hybosoridae (Coleoptera: Scarabaeoidea) from the Yixian Formation of China - Yan, Zhuo; Bai, Ming; Ren, Dong (Zootaxa, 2012)
Hybosoridae is a relatively small family of Scarabaeoidea, including five extant and one fossil subfamily (Ocampo & Ballerio 2006, Nikolajev 2007). Until now, 20 fossil species were known from five subfamilies: Anaidinae, Ceratocanthinae, Hybosorinae, Liparochrinae, and Mimaphodiinae (Ocampo & Ballerio 2006, Krell 2007, Nikolajev 2008, Nikolajev et al. 2010, Nikolajev 2010a, Nikolajev 2010b, Kirejtshuk et al. 2011). In this paper we describe Pulcherhybosorus tridentatus Yan, Bai, & Ren new genus and new species, from a nearly complete and well-preserved fossil. This fossil represents the first record of Hybosoridae from the Early Cretaceous Yixian Formation of Liutiaogou, Inner Mongolia in China. This significant finding tentatively confirms the presence of Hybosoridae during the Mesozoic in what is now China.